Systematic Literature Review (SLR) Strategi Pemasaran Perbankan Syariah Di Indonesia - Hanifa Al Izati; Whilma Lindary; Naufal Afif Putra; Nur Ihsan; Anzu Elvia Zahara (STEKOM PRESS, 2023)
This study aims to conduct a literature review of the results of research on the marketing strategy of Islamic banking in Indonesia. The method used in this study is a Systematic Literature Review (SLR) with a qualitative-descriptive approach, to published journal articles from 2020-2023 obtained from the Google Scholar database on Islamic banking marketing strategies. The results of the discussion of the Systematic Literature Review show that marketing strategy has a very important role in the increasingly fierce competition in Islamic banking by implementing various strategies that can be used for the development of Islamic banking products in Indonesia.